Penguatan Ekonomi Pemuda Berbasis Kearifan Lokal di Kabupaten Aceh Besar - Akmal Saputra; Cut Irna Liyana; Triyanto Triyanto; Wardah Muharriyanti Siregar; Ikhsan Ikhsan; Vellayati Hajad; Iwan Doa Sempena (Universitas Teuku Umar, 2020)
This community service focuses on freshwater fish (catfish) cultivation. This community service is carried out on the basis of youth needs by involving youth or beneficiaries from planning to evaluation. This community service is carried out by paying attention to local wisdom in Gampong Pante Rawa Aceh Besar. The service method used is problem identification, coordination, planning, implementation, monitoring and evaluation. The results of this community service have had a good impact on the youth of Pante Rawa Aceh Besar village, both in economic, social and educational impacts. This community service provides income economically, builds social networks at the village and stakeholder level. This community service also provides new knowledge for youth about freshwater fish farming.